NEW COUNTERPARTS OF SOME INEQUALITIES FOR ENTROPY AND MUTUAL INFORMATION - Dragomir, S. S.; Cho, Y. J.; Choi, Y. K. (Matematichki Bilten, 2000)
In this paper, by the use of a new analytic inequality which counterparts arithmetic mean-geometric mean’s classical inequality, we point out some new results for entropy and mutual information.